Developmental programming: Effect of prenatal steroid excess on intraovarian components of insulin signaling pathway and related proteins in sheep - Ortega, Hugo Hector (2010)
Prenatal testosterone (T) excess increases ovarian follicular recruitment, follicular persistence, insulin resistance, and compensatory hyperinsulinemia. Considering the importance of insulin in ovarian physiology, in this study, using prenatal T-and dihydrotestosterone (DHT, a nonaromatizable androgen)-treated female sheep, we tested the hypothesis that prenatal androgen excess alters the intraovarian insulin signaling cascade and metabolic mediators that have an impact on insulin signaling. Changes in ovarian insulin receptor (INSRB), insulin receptor substrate 1 (IRS1), mammalian target of rapamycin (MTOR), phosphatidylinositol 3-kinase (PIK3), peroxisome proliferator-activated receptor-gamma (PPARG), and adiponectin proteins were determined at fetal (Days 90 and 140), postpubertal (10 mo), and adult (21 mo) ages by immunohistochemistry. Results indicated that these proteins were expressed in granulosa, theca, and stromal compartments, with INSRB, IRS1, PPARG, and adiponectin increasing in parallel with advanced follicular differentiation. Importantly, prenatal T excess induced age-specific changes in PPARG and adiponectin expression, with increased PPARG expression evident during fetal life and decreased antral follicular adiponectin expression during adult life. Comparison of developmental changes in prenatal T and DHT-treated females found that the effects on PPARG were programmed by androgenic actions of T, whereas the effects on adiponectin were likely by its estrogenic action. These results suggest a role for PPARG in the programming of ovarian disruptions by prenatal T excess, including a decrease in antral follicular adiponectin expression and a contributory role for adiponectin in follicular persistence and ovulatory failure.